Hospitalization costs due to healthcare-associated infections: An analysis of propensity score matching - Yu Lv; Lan Chen; Wu Yu J.; Qian Xiang; Qiong S. Tang; Feng D. Wang; Hong M. Cai; Kun Zou; Qiong D. Wei; Hua Z. Zhou; Hui Wang; Chen Wang; et al. (Elsevier, 2019)
Background: In 2018, diagnosis-related group-based prospective payment system (DRG-PPS) was implemented nationwide by China that did not fully consider the additional costs caused by healthcare-associated infections (HAIs). HAIs can increase hospitalization costs, but only a few studies have been conducted in China. We aimed to assess the additional costs caused by HAIs. Methods: A retrospective matched case-control (1:1) study was performed in one of the largest tertiary hospitals in Sichuan Province, China. A multiple linear regression was used to identify confounding factors, and the propensity score matching (PSM) method was used to balance confounding factors between cases and controls. On this basis, we estimated the additional costs caused by HAIs. Results: Of the 109,294 inpatients observed, 1912 had HAI. After the PSM method was implemented, 1686 cases were successfully matched. Median hospitalization costs were €5613.03 for patients with HAIs and €3414.83 for patients without HAIs (P <  0.001), resulting in an absolute difference of €2198.19. With the exception of pathological diagnosis costs, surgical treatment costs and disposable medical material costs for surgery, all other types of costs for the cases with HAIs were larger. Conclusions: Patients with HAIs incurred greater hospitalization costs than non-HAI patients, which warrants closer attention if we are to reform the payment method of medical insurance in China. Keywords: Healthcare-associated infections, Hospitalization costs, Propensity score matching